Detection of Sarcocystis halieti in muscles of raptors from Lithuania - Prakas, Petras; Šukytė, Tautvilė; Juozaitytė-Ngugu, Evelina; Butkauskas, Dalius (Frontiers in veterinary science, 2025)
The genus comprises a diverse group of apicomplexan parasites that infect reptiles, birds, and mammals. They are characterized by the formation of sarcocysts in the muscles of the intermediate host and the development of sporocysts in the intestines of the definitive host. Raptors usually act as definitive hosts for numerous species; however there is a lack of studies on in the muscles of raptorial birds. Therefore, we aimed to assess infection rates and identify species in the muscles of raptors in Lithuania. Muscle samples from 90 raptors (Accipitriformes, Falconiformes, and Strigiformes) were collected throughout Lithuania and analyzed for spp. Sarcocysts isolated from fresh methylene blue-stained muscle samples were identified using the internal transcribed spacer region 1 sequence genetic marker. Under the light microscope, sarcocysts were detected in 8.9% (8/90) of the raptors examined. Sarcocysts were found in the leg muscles of common buzzards ( ), tawny owls ( ), and a long-eared owl ( ); neck muscles of a Eurasian goshawk ( ), rough-legged buzzard ( ), and long-eared owl; and thoracic muscles of a rough-legged buzzard. We observed no sarcocysts in the cardiac muscles. Representatives of one species, . were molecularly identified in seven birds. This is the first study to report five new intermediate hosts for . . Further investigations are needed to assess the possible pathogenicity of . in extra-intestinal organs of raptors.